استيعاب التنشئة التنظيمية في المؤسسات التربوية لدى المعلمين الجدد - شرايطية، أسماء; قادري، حليمة (المركز الجامعي بلحاج بوشعيب عين تموشنت, 2021)
حاولت الدراسة الحالية تناول "استيعاب التنشئة التنظيمية في المؤسسة التربوية لدى المعلمين الجدد" ولتحقيق أهداف الدراسة اعتمدنا على المنهج الوصفي، وباختيار عينة من المعلمين عددهم 40 من قطاع التربية بوهران تم اختيارهم بطريقة عشوائية، طبق عليهم استبيان "التنشئة التنظيمية" صادق وثابت وأعد لأغراض الدراسة، ولمعالجة البيانات استخدمنا عدد من الأساليب الإحصائية: المتوسط الحسابي والانحراف المعياري كما استعملنا اختبار "ت" لدراسة الفروق، وقد أظهرت نتائج الدراسة ما يلي: مستوى استيعاب الموظفين لعملية التنشئة التنظيمية مرتفعة، لا يوجد فروق في استيعاب عملية التنشئة التنظيمية تعزى لمتغير الجنس، يوجد فروق في استيعاب عملية التنشئة التنظيمية تعزى لمتغير الأقدمية.
This Study attempts to investigate the "Assimilation the Social organizational in the educational institution for new teachers", In order to reach the aim of this study, the researcher used the descriptive approach By selecting a sample of 40 new teachers from the education sector in Oran, they were randomly selected, for gathering data was built by the researchers for A valid and reliable questionnaire "Social organizational" the purposes of the study, and applied the next statistical techniques; frequencies, arithmetic means, standard deviations, (t) test, by computer using the statistical package for social sciences (SPSS), The results indicated that: -The level of employee comprehension of the organizational upbringing process is High, -There are no differences statistically significant differences for responses about Social organizational according to the variables of sex, -There are statistically significant differences in Social organizational according to the variables of Experience.
Keywords: المؤسسات التربوية -- الإدارة التعليمية -- التنشئة التنظيمية -- الإدارة التنظيمية -- الاتصال الإداري